The welfare of wildlife: an interdisciplinary analysis of harm in the legal and illegal wildlife trades and possible ways forward - Wyatt, Tanya (Crime, law and social change, 2022)
Wildlife trade - both legal and illegal - is an activity that is currently the focus of global attention. Concerns over the loss of biodiversity, partly stemming from overexploitation, and the corona virus pandemic, likely originating from wildlife trade, are urgent matters. These concerns though centre on people. Only sometimes does the discussion focus on the wildlife traded and their welfare. In this article, we make the case as to why welfare is an important component of any discussion or policy about wildlife trade, not only for the interests of the wildlife, but also for the sake of humans. We detail the harm in the trade as well as the current welfare provisions, particularly in relation to the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), which guide global transport and trade. There are a number of ways that the current approach to wildlife welfare could be improved, and we propose ways forward in this regard.